Beyond the Human Horizon. Issue 1 (1st September 2021) - Mittermaier, Amira
Abstract: Amid a moment of crisis, how might the anthropology of religion shift its focus from ethics to politics? This 2021 Rappaport Lecture, delivered at the Society for the Anthropology of Religion (SAR) Biennial Meeting on 15 May 2021, begins by highlighting three ways in which our field has taken on politics in recent years: by troubling the distinction between ethics and politics, by thinking religion together with pressing political issues, and by taking a critical look at our conceptual horizons. Elaborating on this third way, it proposes that the anthropology of religion needs to move beyond the human horizon by ethnographically grappling with something bigger, namely, God. Prompted by a reflection on the phrase Allāhu akbar (God is the greatest), the lecture maps the challenges posed by a god greater than the human imagination and considers a range of writing strategies that might help make our texts more hospitable to such a figure. Bringing Islam into the conversation about the relationship between theology and anthropology, it suggests that the figure of God directs us toward the evasive and unknowable—that which exceeds our grasp and analysis.